Pengaruh Pemanfaatan Media Lingkungan Sebagai Sumber Belajar Terhadap Hasil Belajar Mata Pelajaran IPA di Madrasah Ibtidaiyah - Muhamad Afandi; Rosa Fadhilah Sari; Kms. Mas'ud Ali (IAI Al Khoziny Buduran Sidoarjo, 2020)
The purpose of this study was to determine the effect of the use of environmental media as a learning resource on the learning outcomes of class III science subjects at MI Al-Amalul Khair Palembang. This type of research is quantitative research with experimental methods and a one group pretest-posttest design research design. The data collection techniques used in this study were tests and documentation. While the data analysis technique used is validity test, reliability test, linearity test, normality test and hypothesis test. Based on the results of data analysis, it shows that the sig value of 0.000 is more than <0.05 and the t count is 10.617, which is greater than the t table at the 5% level, namely 1.699. The results of this data analysis indicate that Ho is rejected and Ha is accepted, which means that there is an influence between the pretest and posttest. So it can be concluded that there is an effect of the use of environmental media as a learning resource on the learning outcomes of class III science subjects at MI Al-Amalul Khair Palembang.